Cross section calculations for neutrino-nucleus reactions at low and intermediate energies. - Chasioti, V. Ch.; Kosmas, T. S.; Divari, P. (HNPS Advances in Nuclear Physics, 2020)
Inelastic neutrino-nucleus reaction cross sections are studied focusing on the neutral current processes. Particularly, we investigate the angular and initial neutrino-energy dependence of the differential and integrated cross sections for low and intermediate energies of the incoming neutrino (or antineutrino). Contributions coming from both, the vector and axial-vector components of the corresponding hadronic currents have been included. The initial and final state nuclear wave-functions have been calculated in the context of the Quasi-particle Random Phase Approximation (QRPA) tested on the reproducibility of the low-lying energy spectrum (up to about 5 MeV) of the studied nuclei. The results presented here refer to the nuclear isotopes 16O and 98Mo. As it is well known, O plays a significant role in supernova evolution phenomena and Mo is used as a target in the MOON neutrino experiment at Japan.